First evidence of fossil snapping shrimps (Alpheidae) in the Neotropical region, with a checklist of the fossil caridean shrimps from the Cenozoic. (November 2020) - Lima, Daniel; Anker, Arthur; Hyžný, Matúš; Kroh, Andreas; Aguilera, Orangel
Abstract: Despite the remarkable diversity and abundance of the modern alpheid shrimps, the fossil record of this group is sparse. However, in defiance of their relatively small size, the fingertips of the snapping claws of Alpheus Fabricius, 1798 have a high fossilisation potential and the preserved structures are highly characteristic. Dactylar and pollex fingertips of snapping shrimps have been recorded by several authors from numerous Cenozoic deposits, ranging from late Oligocene (Chattian, 27–28 Ma) to late Pleistocene (Tarantian, 117–126 ka); however, they have not yet been recorded in the Neotropical deposits. The present study aims to describe in detail a series of isolated snapping claw fragments referable to Alpheus from the Miocene Pirabas Formation, Pará, Brazil. In addition, we briefly discuss the palaeoenvironment, fossil preservation and bioturbation potential of alpheid shrimps. A total of 69 alpheid snapping claw fingertips were obtained from the bulk samples collected in the Atalaia and Aricuru outcrops, representing three distinct morphotypes of dactylar fingertip and at least one morphotype of pollex fingertip, indicating that at least three species of Alpheus inhabited the Cenozoic marine tropical palaeoenvironments of the Atlantic coast of South America. In fact, the presence of different fingertip morphotypes suggests that this group was already diversified in the early-middle Miocene in the Neotropical region and elsewhere. We tentatively attributed the morphotypes from the Pirabas Formation to the A. edwardsii species group, as well as to A. formosus and A. floridanus species complexes. The presence of alpheid shrimps in the Pirabas Formation deposits may be linked to the complex ichnofabric network recorded in this formation. Highlights: Alpheid shrimps inhabited the Cenozoic marine Neotropical palaeoenvironments. Alpheus spp. was already diversified in the Miocene in the tropical America region. Burrowing activity of alpheid may be linked with the Pirabas Formation ichnofabric. Snapping claws of Alpheus have a high fossilisation potential.